Perkembangan Power Tendangan Pencak Silat dengan Latihan Pliometrik - Boris Tubbur Manurung; Murniati Simorangkir; Charly Yonathan Pakpahan; Rahma Dewi; Jan boby Nesra Barus (Mutiara Pendidikan dan Olahraga, 2025)
Plyometric training is a physical training method aimed at improving explosive strength and movement speed, which are crucial in martial arts such as silat. This mini-research aims to analyze the effect of plyometric training on enhancing the quality of kicks in silat, particularly in terms of power, speed, and accuracy. The method used is qualitative, involving a plyometric training program over several weeks applied to individuals learning silat, with performance measurements of kicks taken before and after the intervention. The results show that plyometric training significantly improves lower limb explosive power, coordination, and kicking effectiveness. These findings suggest that plyometrics is an effective training approach and can be integrated into physical development programs, particularly to enhance kicking ability.